Ultrahigh performance PEDOT/Ag2Se/CuAgSe composite film for wearable thermoelectric power generators. (August 2020) - Lu, Y.; Qiu, Y.; Cai, K.; Li, X.; Gao, M.; Jiang, C.; He, J.
Abstract: The thermoelectric (TE) properties of organic/inorganic composite materials have been extensively studied for nearly one decade but there still has no significant breakthrough. Herein, we developed a facile method to prepare poly(3, 4-ethylenedioxythiophene) (PEDOT)/Ag2 Se/CuAgSe ternary composite films with ultrahigh performance and superior flexibility. First, PEDOT:poly(styrenesulfonate) (PSS)–coated Se (PC-Se) nanowires (NWs) were chemically in situ synthesized, then the PC-Se NWs were used as templates to prepare PEDOT:PSS coated Ag2 Se/CuAgSe NWs, and finally highly flexible PEDOT/Ag2 Se/CuAgSe ternary composite films on porous nylon membrane were fabricated by vacuum assisted filtration and then hot pressing. An optimized composite film with hierarchical microstructure defects shows a record power factor (PF) of 1603 μW m −1 K −2 (corresponding 0.6 < ZT < 1.05) at 300 K, which is the record value for TE organic/inorganic composite materials. After bending for 1000 cycles around a 4-mm radius rod, about 92% of the initial PF is maintained, exhibiting an excellent flexibility, which is attributed to the synergetic effect of the flexible nylon membrane, the porous PEDOT/Ag2 Se/CuAgSe film, and specifically the PEDOT as a binder. Moreover, a flexible TE module composed of 11 single-leg of the film generates a voltage of 45.8 mV and a maximum power of 3.2 μW (power density of 8.4 W m −2 ) at a temperature gradient of 36 K, verifying excellent TE properties of the film. This work provides a great idea for design and fabrication of high-performance flexible TE films, which can be extended to other chalcogenides/PEDOT composites and will certainly promote the development and application of TE organic/inorganic composite films. Graphical abstract: Image 1 Highlights: Poly(styrenesulfonate/Ag2 Se/CuAgSe composite film are prepared for the first time using a facile method. The optimized composite film shows ultrahigh thermoelectric (TE) performance. The composite film also exhibits a superior flexibility. A TE generator is designed using the optimized hybrid film. The generator exhibits good flexibility and output performance.